Hybrid solar and grid-connected system with multi-mode operations - Rosnazri, Ali
Solar energy is beginning to take place as the most important alternative energy source in replacing conventional fuels such as crude oil, coal and natural gas. This is due to the increasing of energy demand in which fossil fuels are no longer be able to fulfill future needs because of depleting resources and costly. With the wide installations of solar photovoltaic (PV) cells or solar panels to provide electricity in remote places, homes and buildings, the technology regarding solar electricity is highly demanding. The purpose of this research project particularly introduces to the new concept of solar PV system with multi-mode operations, together with its related components or subsystems, effectively selecting suitable conditions between solar and grid supply in providing electricity to loads. Several advantages and disadvantages of the present stand-alone and grid-connected static inverters are compared with the proposed concept. It introduces to the use of a DC motor and synchronous generator as an electromechanical inverter as an alternative option to present popular approach of using solid-state static inverters in converting the solar DC supply into AC, suitable to run common electrical appliances. This initiates to a more resourceful solar electricity supply system to provide power on different occasions rather than having it to be limited to one dedicated application. As a household benchmark power consumption, the proposed 2 kW output power system is highly versatile, featuring 6 different modes of operation which can be used to function in either grid-connected or offgrid conditions, day and night which could increase the utilizing factor of a solar PV system from 25% to 100% per day . The Main Controller Unit (MCU) with its controlling circuits and programming firmware are specially designed to establish a pioneering fully functional system. The relevant characteristics and parameters of the electromechanical inverter were determined through various simulations and practical procedures. As for the comparative study, performance tests to the static inverters, i.e. modified sinewave, a true sinewave and to the proposed electromechanical inverter were done to evaluate their total harmonics and efficiencies with respect to different load conditions, where the efficiency is determined to be 64% and voltage THD is in between 8.10% to 10.32%. The modified sinewave inverter efficiency is found to be 90.2% with voltage THD is in between 27.64% to 28.97%, while the true sinewave unit efficiency is verified to be 76.1% with voltage THD is in between 2.018% and 3.275%. Actual connection of the designed electromechanical inverter to grid was made with tests data taken to see its performance during parallel operation and off-grid operations. Proper connection of the proposed solar PV system for the most economical way to get better return of investment, proper battery-sizing and isolated generation are extensively discussed. The overall results show that the designed solar PV technology has unique advantages to overcome the weaknesses of present gridconnected solar PV system. As a conclusion, with the realization of such a proposed system, a more versatile PV system that extending the capability of present popular solar PV and grid-connected technology is available as another option for future consideration.